Towards employing metrics in measuring the quality of software safety critical systems and managing their development - Din, Jamilah; Atan, Rodziah; Jusoh, Yusmadi Yah; Jasser, Muhammed Basheer (Engg Journals Publications, 2018)
Failures in safety critical systems have a high impact on the environment in which they are used. For that, developers usually follow specific development standards and techniques to avoid and reduce failures in such systems. Developers have to build safety critical systems considering the quality, complexity, and size factors in all the development phases beginning with the requirement gathering and ending with the maintenance and verification. In this paper, some quality models and some metrics for measuring the quality, complexity, and size of systems are explored. The metrics are classified to the development phases so that the classification indicates the degree of metrics usage in measuring the quality, complexity, and size factors in relation to the development phases. We are now working on relating the studied metrics in this paper with their impact on the development of the software safety critical system. We expect to use these metrics in the management of the development phases and processes of software safety critical systems so that a decision making could be performed based on the measurements of these metrics.